Poetic Speech Analysis of Metaphorical and Literal Uses in War Poetry: A Study of Selected Poems by Wilfred Owen - Shihan Muslih, Waleed; Khamees Khalaf, Meethaq (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims to demonstrate the way by which the use of words helps bring to the front strong poetic effect. In addition, the study deconstructs the structures of the poems, showing the significance of the word usage that generates a striking impact. By metaphorical and literal uses, words function within a linguistic system, creating a direct effect on the reader. So the reader finds himself part of an overlapping structure in Wilfred Edward Salter Owen’s (1893–1918) war poems. Furthermore, two of Owen’s poems, "Strange Meeting(1919) and "Insensibility(1918), have been tackled in this study. Accordingly, the paper concludes that the complexity lies in the figurative use of words; that is, they are contrasting literally.